Programmable Ring Tone Text Transfer Languange Player - Benedictus Herry Suharto (Media Aplikom, 2010)
The aim of this research is to design and implement a programmable Ring Tone Text Transfer Language (RTTTL) player. The system consists of microcontroller hardware that produce custom musics from RTTTL data format that programmable using personal computer (PC). USB (unversal Serial Bus) was used to establish communication between PC and the device, in order to program the music data in the device, so the vary music can be customized by user. The result of the research showed that the music in the device can be played and reprogramming using PC.